2007
DOI: 10.2527/jas.2007-0174
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effect of ractopamine and dietary fat source on quality characteristics of fresh pork bellies1

Abstract: Crossbred pigs (n = 216) were used to test the interaction, if any, of ractopamine (RAC) and dietary fat source on the characteristics of fresh pork bellies. Pigs were blocked by BW (77.6 +/- 6.5 kg) and allotted randomly to pens (6 pigs/pen). After receiving a common diet devoid of RAC for 2 wk, pens within blocks were assigned randomly to 1 of 4 treatments arranged in a 2 x 2 factorial design, with 5% fat (beef tallow vs. soybean oil) and RAC (0 vs. 10 mg/kg). At the conclusion of the 35-d feeding period, pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 45 publications
(58 reference statements)
5
27
0
1
Order By: Relevance
“…Similar results to this study were obtained by Apple et al (2007), who found no significant difference in meat color and fat color in the bellies of pigs receiving 0 and 10 ppm of ractopamine in the diet. Leick et al (2010), analyzing bellies from pigs that received 0 and 5 ppm of ractopamine, did not observe any changes in the fat color parameters L *, a * and b * with the addition of ractopamine; similar results were also found by Carr et al (2005).…”
Section: Resultssupporting
confidence: 80%
“…Similar results to this study were obtained by Apple et al (2007), who found no significant difference in meat color and fat color in the bellies of pigs receiving 0 and 10 ppm of ractopamine in the diet. Leick et al (2010), analyzing bellies from pigs that received 0 and 5 ppm of ractopamine, did not observe any changes in the fat color parameters L *, a * and b * with the addition of ractopamine; similar results were also found by Carr et al (2005).…”
Section: Resultssupporting
confidence: 80%
“…Essa inibição da expressão gênica da leptina pelo uso da ractopamina pode ter ocorrido com os animais utilizados neste trabalho, justificando, assim, a ausência de redução no consumo alimentar. Entretanto, os diversos fatores abordados anteriormente para explicar o consumo alimentar estão em desacordo com outras pesquisas, pois o uso da ractopamina na dieta reduz o consumo de alimento (APPLE et al, 2007), mas não influencia o ganho de peso (MIMBS et al, 2005). Esta redução no consumo estaria relacionada à maior densidade energética das dietas, as quais não alteram o ganho médio diário, mas deprimem o consumo de alimentos (WEBER et al, 2006).…”
Section: Resultsunclassified
“…There was a tendency for a linear increase (P = 0.10) in total MUFA as inclusion of CM-CV increased. Decreased pork fat firmness has been associated with high levels of MUFA and PUFA in pork bellies (Apple et al, 2007;Eggert, Belury, Kempa-Steczko, Mills, & Schinckel, 2001). Pigs fed diets high in MUFA and PUFA have been shown to have bellies with high levels of unsaturated fatty acids (Apple et al, 2007Leick et al, 2010.…”
Section: Fatty Acid Profilesmentioning
confidence: 99%